Economic Impact Analysis of Marine Tourism to Community Revenue - Sri Fitriani Monoarfa; Sri Nuryatin Hamzah; Lis M Yapanto (The NIKe Journal, 2019)
This study aims to determine the economic impact on the income of nautical tourism village community Olele District of Kabila Bone Bone Bolango District. This research was conducted in July-November 2015. The respondents rating determined non-probality sampling, are selected by convenience sampling method. Researchers chose rating arbitrary or accidental encounter. The data collection was done by direct observation using questionnaires. The economic impact was analyzed by using Keynesian Income Multiplier. The results showed that the impact on revenues of maritime tourism Olele village communities are in the category of low and have not been felt evenly. Income Keynesian Multiplier value is 0.99, Type 1 Income Multiplier Ratio is 1.21 and Type 2 Income Multiplier Ratio is 1.67. Direct economic impact in the form of income owners of business units that is equal to 66.27%. While the indirect impact in the form of labor income is still very low at 2.81%. Further impact in the form of labor expenditures amounted to 48.76% is used for food. Keywords: Marine tourism; Keynesian Income Multiplier; economic impact